LEVEL OF KNOWLEDGE AND SKILLS OF SCIENCES TEACHERS REGARDING THE USE OF MULTIMEDIA TEACHING AID FOR SPECIAL EDUCATION STUDENTS WITH VISUAL IMPAIRMENT - Mohd Norazmi, Nordin; Nor Aainaa, Mohd Isa; Siti Mastura, Baharudin; Mohd Saleh, Abbas; Albert Feisal, Muhd Feisal Ismail; Siti Sarah, Maidin; Leha, Saliman (African Journal of Biological Sciences, 2024)
In following the current of education, special education teachers must prepare themselves with high knowledge and solid skills to convey the subject of the lesson to students. Teachers need to be able to master the learning content and deliver it to the students according to their ability level. Teachers need to understand the topic carefully, using clearer language, so that the delivery becomes more effective. Studies explained that the quality of teacher teaching can be improved with high teacher knowledge. In-depth knowledge can help teachers deal with the different abilities and needs of students in the classroom as well as create a good and positive learning environment for students. The ability to teach effectively depends on the knowledge of the teacher. Knowledge can take many forms. Special education teachers need to generate learning knowledge ideas and design interactive multimedia BBM that can motivate students' interests. So along with that, it can create attractiveness in the learning process of the education curriculum. Special.